Spatial mislocalization as a consequence of sequential coding of stimuli. - Priess, Heinz-Werner; Scharlau, Ingrid; Becker, Stefanie I.; Ansorge, Ulrich (Attention, Perception, & Psychophysics)
In three experiments, we tested whether sequentially coding two visual stimuli can create a spatial misperception of a visual moving stimulus. In Experiment 1, we showed that a spatial misperception, the flash-lag effect, is accompanied by a similar temporal misperception of first perceiving the flash and only then a change of the moving stimulus, when in fact the two events were exactly simultaneous. In Experiment 2, we demonstrated that when the spatial misperception of a flash-lag effect is absent, the temporal misperception is also absent. In Experiment 3, we extended these findings and showed that if the stimulus conditions require coding first a flash and subsequently a nearby moving stimulus, a spatial flash-lag effect is found, with the position of the moving stimulus being misperceived as shifted in the direction of its motion, whereas this spatial misperception is reversed so that the moving stimulus is misperceived as shifted in a direction opposite to its motion when the c
Keywords: spatial mislocalization; sequential coding; stimulus parameters; Attention; Discrimination (Psychology); Humans; Judgment; Motion Perception; Optical Illusions; Orientation; Pattern Recognition; Visual; Psychophysics; Space Perception; Cognitive Processes; Motion Perception; Perceptual Localization; Spatial Perception; Stimulus Parameters; Consequence

Perceptual latency priming: A measure of attentional facilitation. - Scharlau, Ingrid (Psychological Research)
The present paper reviews recent research on perceptual latency priming (PLP). PLP is the relative latency advantage--earlier perception--of a visual stimulus that is preceded by another, masked stimulus at its location. The first stimulus attracts attention which accelerates perception of the second stimulus. This facilitation arises even if the first stimulus is visually backward-masked by the second one. The paper summarises research on temporal and spatial properties of PLP and the question whether intentions mediate shifts of attention to external events. Possible sources of PLP besides visuo-spatial attention are discussed. Finally, I give a review of feedforward and reentrant models of PLP and compare them to the empirical evidence. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: perceptual latency priming; attentional facilitation; visuospatial attention; visual backward masking; prior entry; Attention; Humans; Judgment; Reaction Time; Space Perception; Attention; Priming; Response Latency; Visual Masking; Visuospatial Ability

Latency facilitation in temporal-order judgments: Time course of facilitation as a function of judgment type. - Scharlau, Ingrid; Ansorge, Ulrich; Horstmann, Gernot (Acta Psychologica)
The paper is concerned with two models of early visual processing which predict that priming of a visual mask by a preceding masked stimulus speeds up conscious perception of the mask (perceptual latency priming). One model ascribes this speed-up to facilitation by visuo-spatial attention [Scharlau, I., & Neumann, O. (2003a). Perceptual latency priming by masked and unmasked stimuli: Evidence for an attentional explanation. Psychological Research 67, 184-197], the other attributes it to nonspecific upgrading mediated by retino-thalamic and thalamo-cortical pathways [Bachmann, T. (1994). Psychophysiology of visual masking: The fine structure of conscious experience. Commack, NY: Nova Science Publishers]. The models make different predictions about the time course of perceptual latency priming. Four experiments test these predictions. The results provide more support for the attentional than for the upgrading model. The experiments further demonstrate that testing latency facilitation w
Keywords: latency facilitation; temporal order judgments; visual processing; priming; conscious perception; visual mask; Adult; Attention; Female; Humans; Judgment; Male; Perceptual Masking; Reaction Time; Space Perception; Time Perception; Visual Perception; Consciousness States; Judgment; Priming; Visual Masking; Temporal Order (Judgment)